En torno a los hapax de Mosco (Minerva. Revista de Filología Clásica, 2019)
The purpose of this paper is to study the hapax from the poems and fragments supposed to be certainly written by Moschus. In the main, the hapax from Mosch. I Amor fugitivus are descriptive diminutives that shape and confirm the later topic of Eras-Child. In Mosch. II. Europa the most interesting and disputed hapax is θεόταυρος~ which, of course, should be maintained. Among the others, the composed verbs made out from rare simple verbs stand out. The fragments supply five examples and among them δεινοθέτας is specially defended because of the congruency with the context. The conclusion is that the poet doesn't outstand by his exotism in lexical creation, but by his erudition, subtle irony and humour.